1995
DOI: 10.1177/0044118x95026004003
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior, Drug Use, and Aids Knowledge among Midwestern Runaways

Abstract: The authors evaluated sexual behaviors, drug use, and AIDS knowledge among Cleveland runaways (N = 108). Results indicated variable rates of risky sexual behaviors, minimal illicit drug use, and high levels of knowledge about true behavioral risks for HIV infection. These runaways demonstrated less frequent health-compromising sexual behavior and drug use compared to runaways described in other studies. Assumptions should not be made that all runaway youths engage in an unusually high rate of risky behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Based on indepth interviews with homeless youth in the Midwest, we addressed the circumstances surrounding trading sex and the extent to which the decision to do so is voluntary. Although rates of trading sex tend to vary, many studies of homeless adolescents have found prevalence rates for trading sex to be less than 20% (Beech, Meyers, & Beech, 2002;Van Leeuwen et al, 2004;Whitbeck & Hoyt, 1999;Zimet et al, 1995). Similar rates of trading sex have been found among street samples of males and females but higher rates among males in shelter samples (Greene et al, 1999).…”
mentioning
confidence: 89%
“…Based on indepth interviews with homeless youth in the Midwest, we addressed the circumstances surrounding trading sex and the extent to which the decision to do so is voluntary. Although rates of trading sex tend to vary, many studies of homeless adolescents have found prevalence rates for trading sex to be less than 20% (Beech, Meyers, & Beech, 2002;Van Leeuwen et al, 2004;Whitbeck & Hoyt, 1999;Zimet et al, 1995). Similar rates of trading sex have been found among street samples of males and females but higher rates among males in shelter samples (Greene et al, 1999).…”
mentioning
confidence: 89%
“…Homeless youths are particularly vulnerable to contracting HIV and other sexually transmitted diseases (STD)s than their housed counterparts owing to risky sexual behaviors and intravenous drug use (Clatts, Goldsamt, Yi, & Gwadz, 2005;Kral, Molnar, Booth, & Watters, 1997;Zimet & Sobo, 1995). Specifically, early sexual experiences, having multiple sexual partners, and lack of condom use are sexual risk factors associated with HIV and frequently reported among homeless youth (Kral et al, 1997;Rotheram-Borus et al, 1992;Zimet et al, 1995).…”
Section: Hiv/aids and Sexually Transmitted Diseasesmentioning
confidence: 99%
“…Specifically, early sexual experiences, having multiple sexual partners, and lack of condom use are sexual risk factors associated with HIV and frequently reported among homeless youth (Kral et al, 1997;Rotheram-Borus et al, 1992;Zimet et al, 1995). Additionally, engaging in sex work as a means of income and survival on the streets puts homeless youths at further risk for HIV (Lankenau, Clatts, Welle, Goldsamt, & Gwadz, 2005).…”
Section: Hiv/aids and Sexually Transmitted Diseasesmentioning
confidence: 99%
“…Studies have reported that the street life is conducive to drug and alcohol use (Hagan & McCarthy, 1997;Incardi et al, 1993;Kipke et al, 1995cKipke et al, , 1997McCarthy & Hagan, 1992a;Pennbridge et al, 1992;Simons & Whitbeck, 1991;Sherman, 1992;Whitbeck & Hoyt, 1999;Yates et al, 1988;Zimet et al, 1995). Kipke and colleagues (1997) surveyed a representative sample of 432 homeless youth in Los Angeles, California, during 1994 and 1995, using DSM-m criteria to classify alcohol and drug abuse disorders.…”
Section: Situational Factors Influencing Police Contactmentioning
confidence: 99%